Réponses

  • Utilisateur Brainly
2013-10-20T08:44:00+02:00
a) sin(a)=5/13 donc cos(a)=12/13
car sin²(a)+cos²(a)=1

donc tan(a)=5/12
car tan(a)=sin(a)/cos(a)

or tan(2x)=(2tan(x))/(1-tan²(x))
donc (2tan(a/2))/(1-tan²(a/2))=5/12
donc 24tan(a/2)=5-5tan²(a/2)

on pose X=tan(a/2)
donc 5X²+24X-5=0
donc (5X-1)(X+5)=0
donc X=-5 ou X=1/5
donc tan(a/2)=-5 ou tan(a/2)=1/5

 b) cos(a)=3/7 donc sin(a)=2√10/7
donc tan(a)=2√10/3

donc (2tan(a/2))/(1-tan²(a/2))=2√10/3
donc 6tan(a/2)=2√10-2√10tan²(a/2)

avec X=tan(a/2)
2√10X²+6X-2√10=0

donc on en déduit que
tan(a/2)=-√10/2 ou tan(a/2)=√10/5